Prognostic factors of Takotsubo cardiomyopathy: a systematic review. (9th August 2021) - Lu, Xiaojia; Li, Pengyang; Teng, Catherine; Cai, Peng; Jin, Ling; Li, Chenlin; Liu, Qi; Pan, Su; Dixon, Richard A.F.; Wang, Bin
Abstract: Takotsubo cardiomyopathy (TCM), characterized by reversible ventricular dysfunction, has similar mortality to acute coronary syndrome. With the growing interest in the diagnosis of and interventions for TCM, many risk factors had been found to affect the prognosis of TCM patients, such as age, sex, and pre‐existing diseases. Because of the incomplete understanding of the pathophysiologic mechanism in TCM, evidence‐based medical therapy for this condition is lacking. Early intervention on risk factors may improve the outcomes of TCM. In this review, we sought to provide up‐to‐date evidence on risk factors and medical therapies that affect TCM outcome. We found that male sex, physical triggers, and certain comorbidities such as chronic kidney disease, malignant disease, higher body mass index, sepsis, chronic obstructive pulmonary disease, and anaemia were associated with poor TCM prognosis. In contrast, race, hyperlipidaemia, diabetes mellitus, and mood disorders were not clearly associated with TCM prognosis. We also reviewed the effect of medical therapies on TCM outcome, including angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers, β‐blockers, calcium channel blockers, and statins. The evidence that these medications confer a survival benefit on TCM patients is limited. Understanding these prognostic factors could help develop risk‐stratification tools for TCM and establish effective prevention and interventions for this not‐so‐benign condition. Further multicentre clinical studies with large samples and meta‐analyses of findings from previous studies are needed to address the inconsistent findings among the many potential risk factors for TCM.